Quantitative and functional interrogation of parent-of-origin allelic expression biases in the brain - Perez, Julio D; Rubinstein, Nimrod D; Fernandez, Daniel E; Santoro, Stephen W; Needleman, Leigh A; Ho-Shing, Olivia; Choi, John J; Zirlinger, Mariela; Chen, Shau-Kwaun; Liu, Jun S; Dulac, Catherine (eLife, 2015)
The maternal and paternal genomes play different roles in mammalian brains as a result of genomic imprinting, an epigenetic regulation leading to differential expression of the parental alleles of some genes. Here we investigate genomic imprinting in the cerebellum using a newly developed Bayesian statistical model that provides unprecedented transcript-level resolution. We uncover 160 imprinted transcripts, including 41 novel and independently validated imprinted genes. Strikingly, many genes exhibit parentally biased—rather than monoallelic—expression, with different magnitudes according to age, organ, and brain region. Developmental changes in parental bias and overall gene expression are strongly correlated, suggesting combined roles in regulating gene dosage. Finally, brain-specific deletion of the paternal, but not maternal, allele of the paternally-biased Bcl-x, (Bcl2l1) results in loss of specific neuron types, supporting the functional significance of parental biases. These findings reveal the remarkable complexity of genomic imprinting, with important implications for understanding the normal and diseased brain.
Keywords: genomic imprinting; molecular neuroscience; cerebellum; RNA-seq; apoptosis; Bcl-x